Pemerolehan Bahasa Kedua Model Terpimpin: Pembelajaran Bahasa Arab Di Ranting Muhammadiyah Mekarjaya Oleh Ustadz Kahar Chalasta - Zainul Abidin; Abu Bakar Fahmi (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
The emergence of informal Arabic learning in various places has brought new hope for the development of Arabic in Indonesia. Some Arabic lessons are given to students to increase their competence in understanding Arabic texts orally and in writing. However, many Arabic lessons have not maximally utilized Arabic learning materials, methods, and strategies for students appropriately.The selection of appropriate Arabic learning materials, methodologies, and strategies can achieve the objectives of learning Arabic itself. Learning Arabic includes at least three components of language learning and four aspects of skills, namely listening, speaking, reading, and writing. The purpose of this study was to find materials, methods, and strategies for learning Arabic applied in the Muhammadiyah branch of Mekarjaya, Depok City. This research used a qualitative descriptive methodology. The results showed that learning Arabic at the Muhammadiyah Mekarjaya branch used materials, methods, and learning strategies with particular choices.